PENGELOLAAN SAMPAH RUMAH TANGGA DI PERUM BUMI RESIK ABDI NEGARA - Hasanah, Aisa Nurul; Sari, Desi Puspita; Setia, Khairina Milinia; Karwati, Lilis (Jurnal Pengabdian Masyarakat Indonesia, 2024)
The increasing population growth and increasing community activities are the basis for the increase in the amount of waste produced every day, in this case it was carried out with the aim of knowing the management of household waste at Perum Bumi Resik Abdi Negara. Household waste management at Perum Bumi Resik Abdi Negara is still not optimal, in other words, it is still classified as very low because they do not have temporary shelter at home. For this reason, household waste management is being socialized, so that it has value and increases the level of community empowerment.